Holland Family : House Of The Rising Sun - Book 10 - Burke, James Lee 1936-; Patton, Will; Simon & Schuster Audio (Firm) (New York : Simon & Schuster Audio, 2015)
The story of a father and son separated by war and circumstance--and whose encounter with the legendary Holy Grail will change their lives forever.
Keywords: Texas Rangers -- Fiction; Fathers and sons -- Fiction; Voyages and travels -- Fiction; Grail -- Fiction; Audiobooks; Historical fiction; Action and adventure fiction; Audiobooks